1967
DOI: 10.1126/science.156.3781.1484
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13—Rich Diagenetic Carbonates in Miocene Formations of California and Oregon

Abstract: Carbon unusually rich in C(13)(deltaC(13) = +5.4 to +19.0 per mil relative to the Peedee belemnite carbonate standard of the University of Chicago) is characteristic of certain diagenetic limestones and dolomites in the Miocene Monterey Shale of California and the Nye Mudstone of Oregon. This heavy carbon may have originated through low-temperature equilibration between CO(3)- - and CO(2) in migrating carbonated waters or between CH(4) and CO(2) in natural gas. Light carbon (deltaC(13) = -5.6 to -18.2 per mil)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

1971
1971
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 12 publications
1
15
0
1
Order By: Relevance
“…Another more speculative possibility for the enrichment of 13 C in the early atmosphere is that Mars originally had a methane-dominated reduced early atmosphere and minor CO 2 in equilibrium with this atmosphere would have δ 13 C values near +35 h due to the mass balance between CO 2 and CH 4 (Galimov 2000). A similar mechanism has also been proposed for a terrestrial deposit of δ 13 C-rich carbonates (+5.4 h to +19.0 h) associated with natural gas-rich shales (Murata et al 1967). Finally, the possibility exists that the magmatic CO 2 on Mars is substantially enriched in 13 C compared to the Earth.…”
Section: Formation Environments and Insight Into Martian Climate Historymentioning
confidence: 79%
“…Another more speculative possibility for the enrichment of 13 C in the early atmosphere is that Mars originally had a methane-dominated reduced early atmosphere and minor CO 2 in equilibrium with this atmosphere would have δ 13 C values near +35 h due to the mass balance between CO 2 and CH 4 (Galimov 2000). A similar mechanism has also been proposed for a terrestrial deposit of δ 13 C-rich carbonates (+5.4 h to +19.0 h) associated with natural gas-rich shales (Murata et al 1967). Finally, the possibility exists that the magmatic CO 2 on Mars is substantially enriched in 13 C compared to the Earth.…”
Section: Formation Environments and Insight Into Martian Climate Historymentioning
confidence: 79%
“…Muller et al (1972) reported that the primary magnesite and nesquehonite(MgCO 3 3H 2 O) precipitate when the Mg/Ca ratio in the water is greater than 20, whereas dolomite precipitates when the ratio is between 2 and about 12. The Mg/Ca ratio of the seawater is about five, and indeed, dolomite is the most common, magnesium-bearing, diagenetic carbonate found in organic-carbon-rich marine sediments, such as in the Neogene biosiliceous sections of the circum-Pacific region (e.g., Pisciotto and Mahoney, 1981), On'nagawa Formation in northern Japan (Matsumoto and Matsuda, 1987), and the Monterey Formation in California (e.g., Murata et al, 1969;Baker and Burns, 1985). Why did lansfordite or magnesite form instead of dolomite in the upper middle and upper Miocene and Pliocene sediments at Site 799?…”
Section: Lansfordite and Magnesite Formationmentioning
confidence: 99%
“…Dolomite beds and concretions are common in the Miocene to Pliocene siliceous sediments exposed at nearby land sections in northern Japan (On'nagawa and Funakawa Formations and their equivalents) (e.g., Matsumoto and Matsuda, 1987). Miocene Monterey Formation in California also contains numerous dolomite beds and concretions (e.g., Murata et al, 1969Murata et al, ,1972Garrison and Graham., 1984;Kastner et al, 1984). Thus, the diagenetic dolomite is rather common in the Neogene biosiliceous sediments of the circum-Pacific region, and the presence of abundant dolomites in the organic-matter rich, sediments at Site 799 is not surprising.…”
Section: Introductionmentioning
confidence: 99%
“…A second explanation for dolomites with variable heavy carbon and relatively constant heavy oxygen was presented by Murata et al (1969) The isotopic values of the samples from Core 11 and Sidewall Core (SW) 25 are for the diagenetic, platy dolomite. They are not particularly unusual values for a deep-sea dolomite, although the carbon-13 content indicates a partial biogenic origin of CO 2 (Fontes and Desforges, 1975).…”
Section: Lago Mare Carbonatesmentioning
confidence: 99%